An Overview of the Aviation Industry in India with Special Emphasis on Privatization - Pavithra Kumari; P. S. Aithal, (International Journal of Case Studies in Business, IT and Education (IJCSBE), 2020)
Aviation industry in India is presently an expeditious growing industry in India visually perceived according to the report in the last three years. So, India is well-known as the third largest domestic aviation market in the world and is foreseen to be the third largest air passenger market by the end of 2024. To work toward the requirements of the flyers, Government of India is working toward incrementing the number of airports. In 2019, India is reported to have 103 operational airports, with a considerable increase in the airplanes too. The Indian government has plans to invest more to develop the aviation industry with various strategies. Although tremendous achievements are seen recently, still more gaps in development have to be filled. With the increased demand in air travel, India’s aviation industry by 2038 might need 2,380 new commercial airliners. In this paper, the aviation industry in India with special emphasis on privatization process is discussed and analyzed.